Suma De Enteros ¡

Completa ¡

*(-4)+( ) =(-28)*

*( )+(+13)=( +9)*

*(-18) +( ) = (+6)*

*( ) + (+8) = (+6)*

*(+25)+ ( ) =(+12)*

*( ) + (-18) = (-27)*

*(-4) + ( ) = (+15)*

*( ) + (-14) =(-5)*

*(+14) + ( ) = (-9)*

*(+23) + (+42) = ( )*

*(-42) +( ) = (+5)*

*(+11) + (+21) = ( )*

*( ) + (+4) = (-17)*

*(+21) + ( ) = (-6)

*( ) + (+16) = ( -11)

*(+5) +( )= ( - 13)*

*( ) + (-14) = (+3)

*(+13) + ( ) = (-5)*

1

Respuestas

2013-10-10T00:53:51+02:00
*(-4)+(-24 ) =(-28)*
*( -4)+(+13)=( +9)*
*(-18) +( +24)  = (+6)*
*(-2 ) + (+8) = (+6)*
*(+25)+ (  -13) =(+12)*
*(-9 ) + (-18) = (-27)*
*(-4) + (+19 ) = (+15)*
*(  +9) + (-14) =(-5)*
*(+14) + ( -23 ) =  (-9)*
*(+23) + (+42) = (65  )*
*(-42) +( +47 ) = (+5)*
*(+11) + (+21) = (32 )*
*( -21 ) + (+4) = (-17)*
*(+21) + ( -27) = (-6)
*( -27 ) + (+16) = ( -11)
*(+5) +(-18  )= ( - 13)*
*(  +17) + (-14) =  (+3)
*(+13) + ( -18 ) = (-5)*